2012
DOI: 10.1007/s11999-011-2136-z
|View full text |Cite
|
Sign up to set email alerts
|

Limited Intraobserver and Interobserver Reliability for the Common Measures of Hip Joint Congruency Used in Dysplasia

Abstract: Background A congruent hip frequently is cited in the literature as a prerequisite for performing a reconstructive pelvic osteotomy for hip dysplasia. The designation as congruent is important as incongruent joints generally are regarded as requiring a salvage-type procedure. Several measures of congruency are described in the literature, but it is unclear whether these measures are reliable. Questions/purposes We therefore evaluated the intraobserver and interobserver reliabilities of three measures of hip co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…The dysplastic hip has been described qualitatively as less congruent than the normal hip based on two-dimensional radiographs [17, 18]. This qualitative description has resulted in poor inter- and intra-observer reliability in reporting congruency in dysplastic hips [19, 20]. Further, congruency has previously been described globally and only on the bony surfaces [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The dysplastic hip has been described qualitatively as less congruent than the normal hip based on two-dimensional radiographs [17, 18]. This qualitative description has resulted in poor inter- and intra-observer reliability in reporting congruency in dysplastic hips [19, 20]. Further, congruency has previously been described globally and only on the bony surfaces [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is always uncertainty in measureing bony parameters for unsure margin of the bony acetabulum [10]. In our study, congruence of articulating is seen at every position in the normal hip joint during development.…”
Section: Discussionmentioning
confidence: 57%
“…Margin of the bony acetabulum was hard to identify in some cases for irregular ossification. There is similar trouble when we measure acetabular angle (AA) in radiography, which result in inaccurate quantitative evaluation [10]. Base on the ball-and-socket shape the hip joint, radial scanning through the centre of femoral head can better reflect the physiological status of the joint.…”
Section: Discussionmentioning
confidence: 99%
“…Interobserver reliability of these measurements was excellent for preoperative radiographs but dropped to moderate for the postoperative radiographs. One author referenced review of several methods of measuring hip joint congruity of Larson et al 77 in a hip dysplasia population. 54 Larson et al found poor intra-and interobserver reliabilities of these methods, and they have not been described in an acetabular fracture population.…”
Section: Discussionmentioning
confidence: 99%
“…9,28,77 Their work demonstrates that CT scans are more accurate at identifying residual articular steps and gaps at the joint surface after surgery when compared with plain radiography. In the largest study, however, Archdeacon et al found that management was changed in only 2.5% of cases based on the postoperative CT scan.…”
Section: Discussionmentioning
confidence: 99%